Development of Tartaric Acid Derived Hydrogen-Bond Donors - Lauber, Markus Boris; Fröhlich, Roland; Paradies, Jan (Synthesis, 2012)
A flexible synthesis of bifunctional thiourea derivatives based on the TADDOL framework is described. Hydroxy as well as primary, secondary, and tertiary amino-substituted bifunctional hydrogen-bond donors were synthesized.
Keywords: TADDOL; thiourea; hydrogen bond; asymmetric synthesis; catalyst